Indigo : a Valentino mystery - Estleman, Loren D. (Estleman, Loren D. Valentino mystery., 2020)
Collecting a valuable, never-before-released noir film that was shelved for its possible mob ties, film detective Valentino searches for clues about the film's believed-dead star as part of a mainstream marketing campaign.